Antimicrobial Susceptibilities, Its Resistance Mechanisms, Virulence Determinants and Phylogenetic Groups of Escherichia coli Isolated From Different Clinical Animal Samples - Aslantaş, Ö; Sakin, F; Bayırlı Nacaroğlu, M; Keskin, O; Güllü Yücetepe, AS; Celic, BG; Şengül, SA (Journal of the Hellenic Veterinary Medical Society, 2025)
Escherichia coli is a versatile agent, as some are commensals, normally living in the intestines of both humans and animals, while others are pathogenically responsible for a wide variety of intestinal and extra-intestinal infections including urinary tract infections (UTIs), meningitis, septicemia, bovine mastitis and colibacillosis in poultry. The present study aims to determine the antimicrobial susceptibilities, its underlying genetic resistance mechanisms, distribution of phylogroups, and virulence determinants of 42 E. coli isolates from different clinical sources of animals. Our results have revealed that phylogroup A1 (42.9%) and B1 (40.5%) were the most prevalent phylogenetic groups with different virulence profiles and varying incidence of virulence determinants. High rates of resistance to different categories of antimicrobial agents with high rate of MDR (59.5%). Phylogenetic analysis showcased remarkable diversity among the tested isolates, with no discernible clustering based on antimicrobial resistance or virulence patterns. Our research has demonstrated the significant phylogenetic diversity of E. coli isolated from different clinical samples. E. coli isolates are endowed with various virulence factors that contribute to their pathogenesis in animals. The elevated rates of antimicrobial resistance and emergence of MDR mirror the trend detected globally in recent years.